2018
DOI: 10.2147/idr.s178717
|View full text |Cite|
|
Sign up to set email alerts
|

An increasing trend of neonatal invasive multidrug-resistant group B streptococcus infections in southern China, 2011–2017

Abstract: BackgroundA multidrug-resistant (MDR) RR2 gene cluster was identified by whole-genome sequencing in several highly virulent (ST-17) Group B streptococcus (GBS) isolates, which caused neonatal invasive infections in southern China in 2016. Tracing the transmission and distribution of MDR isolates in this area is important for the effective management of future infections. The aim of this study was to obtain longitudinal data of MDR isolates to monitor epidemiological trends of general common isolates in souther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 32 publications
2
11
0
Order By: Relevance
“…In the present study, the colonization rate of GBS was 7.27%. Our findings agreed with the results in two reports from Chengdu and Beijing [10,11]. Similar findings were also reported from those in Japan, Malaysian and Korea whose colonization rates of GBS are 8.2%, 7.5% and 8.0% respectively [12][13][14].…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, the colonization rate of GBS was 7.27%. Our findings agreed with the results in two reports from Chengdu and Beijing [10,11]. Similar findings were also reported from those in Japan, Malaysian and Korea whose colonization rates of GBS are 8.2%, 7.5% and 8.0% respectively [12][13][14].…”
Section: Discussionsupporting
confidence: 93%
“…Antibiotic susceptibilities reported in different studies from the same region might corroborate each other. A recent study from Guangzhou showed an increasing trend of multidrug-resistant bacteria in neonatal invasive infections 34. Another study conducted in Guangzhou also reported the high and continuously increasing resistance rates among Gram-positive bacteria 35.…”
Section: Discussionmentioning
confidence: 99%
“…However, the high incidence rate of extended-spectrum β-lactamase producers and the high resistance to ampicillin and the third-generation cephalosporins continue to suggest that serious concern is warranted. Regardless of the high resistance reported consistently to erythromycin or clindamycin, penicillin or ampicillin is effective against GBS in China 5,21,26. In general, empirical therapy should be guided by the antimicrobial resistance patterns of bacterial isolates commonly detected.…”
Section: Discussionmentioning
confidence: 99%